Historical Approach to the Role of Women in the Legislation of Iran: A Case Study on the Twenty-First Parliament - Sheibani, Sarah; Jalalpour, Shiva (Journal of History Culture and Art Research, 2017)
One hundred and ten years ago, men and women took constitutionalism to achieve justice in Iran. National Council was the result of the Iranian people’s struggle for justice, both women and men. Men policies from the beginning of legislation put women as minors and lunatics and bankrupted and banned them from vote. However, the Constitutional Revolution as a turning point and a national revolution played a key role in changing attitudes to women and structural context of their participation provided. In this paper, with the use of descriptive-analytical as well as quantitative methods, we sought to answer the question that what was the position of women in the twenty-first Parliament. The results of this study suggest that when Iranian women were allowed to participate politics, they have achieved to show their ability in politics as we saw examples in the twenty-first Parliament in which women had twenty-two percent participation.